Pengembangan Media Hologram Berbasis Fan Projection untuk Meningkatkan Minat Belajar Siswa Kelas VII - Fausan, Aswat Ahmad; Fakhrunnisaa, Nur (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
The research discusses the development of fan projection-based hologram media in increasing learning interest in class VII MTs N Palopo City. The research aims to determine the stages of media development, to find out whether it is valid or not in increasing students' learning interest in prayer procedures material. The research uses the R&D (Research and Development) type, and the ADDIE model stages: Analysis Design, Development, Implementation, Evaluation. Subject students in class VII.H MTs N Palopo City. This research uses data collection techniques by means of interviews, questionnaires and documentation. The data analysis used is qualitative and quantitative. The results of the research obtained validation results from media experts 93%